Phenomenological Study Of Teachers' Perception Of Canva As A Learning Aid - Irwan Hermansah; Jajang Ahmad Nurdin; Rini Rosmiati; Noneng Yuningsih; Deni Darmawan (UNIVERSITAS PAKUAN, 2024)
Study This aiming disclose in a way deep how teachers give meaning in experience they moment implementing Canva in practice learning everyday. In addition, research this will also identify challenges faced and Canva 's potential in increase quality learning from teacher perspective. Qualitative methods descriptive approach phenomenological become choice in carry out study This. Data is collected using technique questionnaire distributed in a way wide and open through social media. For five months the data was collected as many as 178 respondents consists of on elementary, middle, and high school teachers. The results of the study show that, 1) as many as 177 teachers have know application canva, 172 teachers have use it in learning, as well as 2 teachers who have not Can operate use canva. Intensity use canva which states very often only as many as 32 teachers, while 65 teachers often, and 81 teachers sometimes ; 2) type projects used by teachers in utilise application canva in three the most, namely presentations, posters, and videos; 3) advantages and disadvantages from application canva according to the teachers, namely, easy used, its features interesting, more modern and sophisticated, the availability of many and varied templates. Meanwhile, the drawbacks is limit exploration of original design ideas, requires internet network no Can done in a way offline. 4) benefits felt by teachers in use application canva, is very helpful in create active, creative and interesting learning media so that KBM is more interesting interest participant educate, facilitate educator in make device learning. 5) Teacher's impression of use application canva, very fun, satisfying, very helpful, and fascinating.